EVALUASI HASIL PRODUK PEMBELAJARAN MEMBACA PUISI KELAS X MATA PELAJARAN BAHASA INDONESIA DI SMAN 1 BUMIAYU - Rizqillah, Septy; Irma, Cintya Nurika (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2025)
This research is program evaluation research, especially on the product component of the CIPP model evaluation using a qualitative approach. The aim of this research is to identify and evaluate the results of the product implementation of poetry reading learning taught in class X at SMAN 1 Bumiayu. Data collection techniques in this research used observation techniques, interview techniques, questionnaire techniques, and document techniques. The instruments used were observation instruments in the implementation of learning to read poetry, interview instruments, questionnaire instruments, and document instruments. The data analysis technique starts with data collection, the data is reduced, next is data presentation, and finally, conclusions are drawn. Based on the results of observations and interviews conducted with the head, head of curriculum, class X Indonesian language subject teacher, and student representatives, one of the results obtained was the product components in the implementation of the class These product components obtain answers to the suitability of learning with the learning outcomes of class X poetry reading at SMAN 1 Bumiayu. Based on the results of the research, recommendations were obtained which can be used as material for consideration in improving the teaching of reading poetry in class for teachers includes the use of social media as part of technology and strengthening students' abilities in reading poetry through training, and (3) recommendations for students is to increase understanding of the meaning of the poetry they read. Keywords: evaluation of programs, products, implementation of learning, reading poetry